Assessment Of Risk Factors and Measures to Prevent Exposure to Harmful Substances and Physical Stress in The Production Of Mineral Fertilizers (Eurasian Medical Research Periodical, 2024)
This article discusses important aspects of safety and occupational health in the production of mineral fertilizers. Potential hazards posed by chemical substances, dust, gases, and physical strains at workstations in fertilizer manufacturing workshops are examined. The possible negative health consequences for employees, such as respiratory irritation, skin and eye irritation, allergic reactions, joint injuries, etc., are reviewed. Methods for preventing these hazards are outlined, including the use of personal protective equipment, training in safe work practices, organizing workspaces, and regularly monitoring levels of harmful substances. The importance of proper lifting and handling techniques, preventing repetitive motions, and caring for the spine to reduce the risk of injuries and joint wear is discussed. Key measures to ensure the safety and wellbeing of employees in fertilizer production are highlighted.